2022
DOI: 10.1038/s41598-022-06022-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of Mycobacterium avium complex pulmonary disease according to disease severity

Abstract: Mycobacterium avium complex pulmonary disease (MAC-PD) requires long-term treatment. We analyzed the outcomes of 992 MAC-PD patients according to disease severity and compared the outcomes of intermittent and daily therapy for mild disease. Patients were divided into groups according to severity using the body mass index, age, cavity, erythrocyte sedimentation rate, and sex (BACES) system, and culture conversion rates were evaluated. We also evaluated the effects of intermittent treatment on the culture conver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Only patients with MAC-PD treated with the M + R + EMB-based regimen showed a higher microbiological cure rate. The culture-negative conversion rate in our study was 31%, which was lower than that in previous studies ( 16 ). This lower conversion rate may be because only 69% of patients received M + R + EMB-based regimens and the relatively short treatment duration of 324 days.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Only patients with MAC-PD treated with the M + R + EMB-based regimen showed a higher microbiological cure rate. The culture-negative conversion rate in our study was 31%, which was lower than that in previous studies ( 16 ). This lower conversion rate may be because only 69% of patients received M + R + EMB-based regimens and the relatively short treatment duration of 324 days.…”
Section: Discussioncontrasting
confidence: 88%
“…Treatment durations of <12 months had similar success rates (66%) to treatment durations of ≥12 months (68%) ( 11 ). A South Korean cohort found a 61%–85% sputum culture conversion rate for MAD-PD patients treated with an M + R + EMB-based regimen for ≥12 months ( 16 ). However, the evidence supporting this treatment duration is limited.…”
Section: Discussionmentioning
confidence: 99%
“…BACES severity was originally developed as an indicator that reflects the survival rates of NTM-PD patients [26]. It is known that BACES severe patients have a higher mortality rate compared to BACES mild patients, and this finding has been consistent not only in South Korea study but also in recent validation studies conducted in Canada [27,28,31]. Furthermore, recent studies have reported that treatment responses vary depending on the severity of BACES, with BACES severe patients showing lower cure rates compared to those with BACES mild [27,28].…”
Section: Discussionmentioning
confidence: 59%
“…NTM-PD severity was determined using the BACES score [body mass index < 18.5 kg/m 2 , age ≥ 65 years, presence of cavity, elevated erythrocyte sedimentation rate (ESR) in men > 15 mm/h and in women > 20 mm/h, and male sex; each worth one point]. One point was assigned for each item, and the total score was considered an indicator of mild (0-1 point), moderate (2-3 points), or severe (4-5 points) disease [26][27][28].…”
Section: Data Collectionmentioning
confidence: 99%
“…However, there are limited data on the role of the microbiome in the course of NTM-PD. [11,12] Therefore, this study compared the bacterial microbiomes in the sputum of NTM-PD patients who remained stable without antibiotics and those who required treatment for disease progression to determine whether there were signi cant differences in the microbiomes of the two groups and, in particular, to evaluate the characteristics of the respiratory microbial environment in NTM-PD patients with stable clinical status. We believe that our ndings will improve our understanding of how the respiratory microbial environment in uences the course of NTM-PD.…”
mentioning
confidence: 99%